Shared risk factors for COVID‐19 and preeclampsia in the first trimester: An observational study. (3rd May 2022) - Serrano, Berta; Mendoza, Manel; Garcia‐Aguilar, Paula; Bonacina, Erika; Garcia‐Ruiz, Itziar; Garcia‐Manau, Pablo; Gil, Judit; Armengol‐Alsina, Mireia; Fernandez‐Hidalgo, Nuria; Sulleiro, Elena; Lopez‐Martinez, Rosa Maria; Ricart, Marta; et al.
Abstract: Introduction: The association between preeclampsia and coronavirus disease 2019 (COVID‐19) is under study. Previous publications have hypothesized the existence of shared risk factors for both conditions or a deficient trophoblastic invasion as possible explanations for this association. The primary aim of this study was to examine baseline risk factors measured in the first‐trimester combined screening for preeclampsia in pregnant women with COVID‐19 compared with the general population. A secondary aim of this study was to compare risk factors among patients with mild and severe COVID‐19. Material and Methods: This was an observational retrospective study conducted at Vall d'Hebron Hospital Campus (Catalonia, Spain). Study patients were 231 pregnant women undergoing the first‐trimester screening for preeclampsia and positive for severe acute respiratory syndrome coronavirus 2 between February 2020 and September 2021. The reference cohort were 13 033 women of the general population from six centers across Catalonia from May 2019 to June 2021. Based on the need for hospitalization, patients were classified in two groups: mild and severe COVID‐19. First‐trimester screening for preeclampsia included maternal history, mean arterial blood pressure, mean uterine artery pulsatility index (UtAPI), placental growth factor (PlGF), and pregnancy‐associated plasma protein‐A (PAPP‐A). Results: The proportion of cases at high risk for preeclampsia was significantly higher among the COVID‐19 group compared with the general population (19.0% and 13.2%, respectively; p  = 0.012). When analyzing risk factors for preeclampsia individually, women with COVID‐19 had higher median body mass index (25.2 vs 24.5, p  = 0.041), higher UtAPI multiple of the median (MoM) (1.08 vs 1.00, p  < 0.001), higher incidence of chronic hypertension (2.8% vs 0.9%, p  = 0.015), and there were fewer smokers (5.7% vs 11.6%, p  = 0.007). The MoMs of PlGF and PAPP‐A did not differ significantly between both groups (0.96 vs 0.97, p  = 0.760 and 1.00 vs 1.01, p  = 0.432; respectively). Conclusions: In patients with COVID‐19, there was a higher proportion of women at high risk for preeclampsia at the first‐trimester screening than in the general population, mainly because of maternal risk factors, rather than placental signs of a deficient trophoblastic invasion.